Increased Serum Soluble Transferrin Receptor Levels Were Associated With High Prevalence of Cardiovascular Diseases: Insights From the National Health and Nutrition Examination Survey 2017–2018 - Zhu, Shiyu; Liu, Chang; Zhao, Chengchen; Chen, Guanzhong; Meng, Simin; Hong, Ma; Xiang, Meixiang; Xie, Yao (Frontiers in Cell and Developmental Biology, 2022)
Background: Iron deficiency is common in cardiovascular diseases (CVD), e.g. heart failure and coronary heart disease. Soluble transferrin receptor (sTfR) is a promising marker representing unmet cellular iron demands. However, whether higher serum sTfR is associated with increased risk of CVDs needs further investigation. Methods: In the present cross-sectional study, we analyzed data of 4,867 adult participants of the National Health and Nutrition Examination Survey (NHANES) 2017-2018. Linear regression models were employed to identify possible correlations between sTfR and other characteristics. The association between sTfR and CVDs was assessed with univariable and multivariable logistics regression models. Results: The prevalence of CVDs was 9.5% among participants, and higher sTfR levels were found in participants with CVDs (p<0.001). Linear regression models revealed positive associations between sTfR and age, body mass index, systolic blood pressure, glycated hemoglobulin A1c, and insulin resistance (all p<0.001). In the multivariable logistics regression model, the adjusted odds ratio of sTfR for CVDs was 2.05 (per 1 log2 mg/L, 95% confidence interval: 1.03 4.05, p=0.046). Further subgroup analysis identified the associations of sTfR and CVDs were only significant in participants ≥60 years old, or with hypertension (all p<0.05). Conclusion: Our study demonstrated that increased serum sTfR levels were associated with a high prevalence of cardiovascular diseases.